Hubungan antara Jenis Kelamin, Asupan Serat, Asupan Cairan, Aktivitas Fisik dan Konstipasi Fungsional pada Karyawan - Falasiva, Rezyta; Kurniasari, Kurniasari (An Idea Health Journal, 2025)
Constipation is a health problem that affects the quality of life of individuals. Gender, fiber intake, fluid intake and physical activity are factors that affect the incidence of constipation. Employees with busy or irregular working hours often have unhealthy lifestyles, including a low-fiber diet, low drinking water consumption and high sedentary behavior. This study aims to analyze the relationship between fiber intake, fluid intake, and physical activity with the incidence of constipation in employees. A total of 130 employees aged 20 – 60 years, who had no history of illness and medication that can cause constipation and were not pregnant, were included in this study. Fiber and fluid intake data were collected using the Food Frequency Questionnaire (FFQ) while data on physical activity was assessed using the International Physical Activity Questionnaire (IPAQ). The diagnosis of functional constipation was determined using the diagnostic criteria from ROME III. The analysis was carried out using the Chi-square test and the significance level was 95%. This study found a relationship between fiber intake, fluid intake, and physical activity with the incidence of functional constipation (p=0.03; p=0.05; p<0.001), but did not find a relationship between sex and the incidence of functional constipation (p=0.18). Functional constipation in employees can be affected by fiber intake, fluid intake and physical activity of the employee, but not by gender